Respostas
respondido por:
1
A) X(X - 1 ) (X - 2 )
(X² - X) (X - 2 ) = X³ - 2 X² - X² + 2 X = X³ - 3 X² + 2 X
B)3 X(X - 1 )= 3 X² - 3 X
C)5 + 6 X - 2 X = 5 + 4 X
D)2(X - 3 )² + 5 =
2 (X² - 2 X 3 + 3²) + 5 =
2(X² - 6 X + 9 ) + 5 =
2 X² - 12 X + 18 + 5 =
2 X² - 12 X + 23
(X² - X) (X - 2 ) = X³ - 2 X² - X² + 2 X = X³ - 3 X² + 2 X
B)3 X(X - 1 )= 3 X² - 3 X
C)5 + 6 X - 2 X = 5 + 4 X
D)2(X - 3 )² + 5 =
2 (X² - 2 X 3 + 3²) + 5 =
2(X² - 6 X + 9 ) + 5 =
2 X² - 12 X + 18 + 5 =
2 X² - 12 X + 23
adlizinha2014:
De nada,bons estudos : )
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás